Application and Suggestions of Morpholine Ring as a Lysosome Targeting Group - Xuelian Liu; Ximeng Zhang; Yinghong Han; Xingrui Li; Jinyao Li (Chemistry, 2025)
Lysosomes are widely present in eukaryotic cells and play an extremely important role in cell growth and development, and their dysfunction is closely related to a variety of diseases. The development of a precise lysosomal targeting strategies is of great significance for the detection of lysosomal physiological functions and the diagnosis and treatment of related diseases. Morpholino ring modification has become a commonly used lysosomal targeting strategy, but its effects have not been systematically evaluated. This review summarizes the effects of morpholine rings in fluorescent probes in recent years. The results show that morpholine rings as lysosomal targeting groups have excellent structural adaptability, but their localization effect is influenced by the log p value and charge of the overall molecule, and this effect has structural differences. In addition, since the morpholino ring is essentially an acidic microenvironmental targeting moiety, it carries the risk of off-targeting to other acidic sites.